Resolving spatiotemporal dynamics in bacterial multicellular populations: approaches and challenges - Miranda, Suyen Solange Espinoza; Abbaszade, Gorkhmaz; Hess, Wolfgang R.; Drescher, Knut; Saliba, Antoine Emmanuel; Zaburdaev, Vasily; Chai, Liraz; Dreisewerd, Klaus; Grünberger, Alexander; Westendorf, Christian; Müller, Susann; Mascher, Thorsten (Microbiology and Molecular Biology Reviews, 2025)
SUMMARY The development of multicellularity represents a key evolutionary transition that is crucial for the emergence of complex life forms. Although multicellularity has traditionally been studied in eukaryotes, it originates in prokaryotes. Coordinated aggregation of individual cells within the confines of a colony results in emerging, higher-level functions that benefit the population as a whole. During colony differentiation, an almost infinite number of ecological and physiological population-forming forces are at work, creating complex, intricate colony structures with divergent functions. Understanding the assembly and dynamics of such populations requires resolving individual cells or cell groups within such macroscopic structures. Addressing how each cell contributes to the collective action requires pushing the resolution boundaries of key technologies that will be presented in this review. In particular, single-cell techniques provide powerful tools for studying bacterial multicellularity with unprecedented spatial and temporal resolution. These advancements include novel microscopic techniques, mass spectrometry imaging, flow cytometry, spatial transcriptomics, single-bacteria RNA sequencing, and the integration of spatiotemporal transcriptomics with microscopy, alongside advanced microfluidic cultivation systems. This review encourages exploring the synergistic potential of the new technologies in the study of bacterial multicellularity, with a particular focus on individuals in differentiated bacterial biofilms (colonies). It highlights how resolving population structures at the single-cell level and understanding their respective functions can elucidate the overarching functions of bacterial multicellular populations.
CRIS-Team Scopus Importer:2025-04-11
Keywords: cell differentiation; microbial multicellularity; phenotypic heterogeneity; population dynamics; population ecology; single-cell technologies; single-cell transcriptomics